Clinical Significance of Low Density Lipoprotein Cholesterol Measurements: Direct Versus Indirect Method - Sharma, Manushri; Batra, HS; Banerjee, Mithu; Bhattarai, Arabinda Mohan; Agarwal, Deeptika (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Estimation of low density lipoprotein cholesterol (LDL-C) is crucial in management of coronary artery disease patients. The management of dyslipidemia is largely based on the concentration of LDL-C. The objective of this study was to compare direct measurement of LDL-C determined by a homogenous method with LDL-C estimation done by Friedewald formula (FF) in heterogeneous populations. Methods: In this cross sectional study, we measured LDL-C by homogenous method (D-LDL-C) in 1,000 fasting samples & compared with FF (F–LDL-C) used for calculation of LDL-C. The measurements of total cholesterol (TC) and triglycerides (TG) were performed using traditional enzymatic methods. The measurements of high density lipoprotein cholesterol (HDL-C) and LDL-C were performed using direct methods with precipitation, and the estimation of the LDL-C fraction was calculated using the FF. Results: Correlation analysis shows that the two methods had significant correlation (p